TEACHERS' GRADING DECISION MAKING - Isnawati, Ida; Saukah, Ali (TEFLIN Journal, 2017)
This study investigated teachers' grading decision making, focusing on their beliefs underlying their grading decision making, their grading practices and assessment types, and factors they considered in grading decision making. Two teachers from two junior high schools applying different curriculum policies in grade reporting in Indonesian educational context were interviewed in depth to reveal their grading decision making. The results show that the teachers believe that assigning grades is not only for measuring the students' ability, but also for making them active users of the language, giving them life skills and experience and motivating them. In addition, these teachers use various grading practices involving not only formal assessment but also informal one. Remedial tests, giving more tasks and grade adjustment are also done to reach the criteria of passing grade. The factors considered in grading decision making are achievement factors in the forms of scores from formal and informal assessment and non-achievement factors involving students' effort and behavior, curriculum and school policy.